A study to assess the association between early childhood caries and relationship of Streptococcus mutans in saliva of mother, child and sibling pairs - Avanti, Ashwini; Avanthi, Sucheeth; P. K., Shivaprakash; Raj H., Kiran; Saini, Sawinderjith; Naik, Pooja M. (International Journal of Contemporary Pediatrics, 2019)
Background: Early childhood caries (ECC) is a specific form of rampant caries that initially affects the primary maxillary anterior teeth of infants and children. According to American Academy of Pediatric Dentistry (AAPD) 2011, early childhood caries is defined as the presence of one or more decayed (non-cavitated or cavitated lesions), missing (due to caries) or filled tooth surfaces in any primary tooth in a child under the age of six. The objective of this study was to assess the association between early childhood caries and relationship of Streptococcus mutans in saliva of mother, child and sibling pairs. Methods: Group 1 consists of fifty children with early childhood caries along with their mothers and siblings with the child age between 15 months to 5 years and sibling’s age between 4 years to 10 years, whereas group 2 consists of fifty caries free children along with their mothers and siblings. For both groups, saliva samples were taken from the child, mother and sibling pairs to estimate the Streptococcus mutans count and to determine pH of saliva in these children. DMFT scores, debris scores checked for child, mother and sibling pairs. Results: Streptococcus mutans count was significantly high in group 1 than that of the group 2. Mothers were more co related to the children in the acquisition of Streptococcus mutans than the siblings. Increased no of meals of the child, pacifier use, low socio-economic status and low maternal education showed significant high correlation with caries prevalence. Low pH score was also significantly correlated with the increase in caries rate. Conclusions: Maternal factors such as high DMFT scores, low education levels, prolonged bottle-feeding with sweetened milk, pacifier use are strong risk indicators for identifying high caries-susceptible children.